Doxorubicin-Induced Cognitive Impairment: The Mechanistic Insights - Du, Jiajia; Zhang, Aoxue; Li, Jing; Liu, Xin; Wu, Shuai; Wang, Bin; Wang, Yanhong; Jia, Hongyan (Frontiers in Oncology, 2021)
Chemotherapy can significantly prolong the survival of patients with breast cancer; Nevertheless, the majority of patients receiving chemotherapy such as doxorubicin may have cognitive deficits that manifest as impairments in learning, reasoning, attention, and memory. The phenomenon of chemotherapy-induced cognitive decline is termed as chemotherapy-related cognitive impairment (CRCI) or chemo-brain. Doxorubicin (DOX), a commonly used drug in adjuvant chemotherapy for patients with breast cancer, has been reported to induce chemo-brain through a variety of mechanisms including DNA damage, oxidative stress, inflammation, dysregulation of apoptosis and autophagy, altered level of neurotransmitter, mitochondrial dysfunction, glial cell interactions, neurogenesis inhibition, and epigenetic factors. These mechanisms do not operate independently but are inter-relate, coordinately contributing to the development of the chemo-brain. This Here we review the relationships of these mechanisms and pathways in attempt to provide mechanistic insights into the doxorubicin-induced cognitive impairment.